Short-term Efficacy Comparison of High-intensity and Low-intensity Laser Therapy in the Treatment of Lateral Epicondylitis: A Randomized Double-blind Clinical Study - Ercan KAYDOK; Banu ORDAHAN; Sezin SOLUM; Ali Yavuz KARAHAN (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate and compare the short-term efficacies of high-intensity laser therapy (HILT) and low-intensity laser therapy (LILT) in the treatment of lateral epicondylitis (LE). Patients and methods: Sixty patients (16 males, 44 females; mean age 44.2±9.3 years; range, 18 to 65 years) with unilateral elbow pain were randomized into two groups as 30 patients treated with HILT (9 males and 21 females) and 30 patients treated with LILT (7 males and 23 females). The HILT (1,064 nm) and LILT (904 nm) were administered three times a week for three weeks, and each treatment was combined with an epicondylitis bandage. A visual analog scale (VAS), quick Disabilities of the Arm, Shoulder, and Hand (QDASH) questionnaire, Medical Outcomes Study Questionnaire Short Form 36 Health Survey (SF-36), and hand grip strength test were used to evaluate the patients before and three weeks after treatment. Results: The two groups had similar demographic characteristics, including age, sex, occupation, and body mass index (p>0.05). There were no statistically significant differences between the two groups in terms of the pretreatment VAS, QDASH, hand grip strength, and SF-36 scores (p>0.05). After three weeks, both groups showed significant improvements in all of the parameters (p<0.05). However, in the HILT group, the QDASH, hand grip strength, and SF-36 physical component summary (PCS) scores showed superior improvement compared to the LILT group (p<0.05). Conclusion: Each treatment modality was found to be effective and safe for the short-term treatment of LE. However, the HILT exhibited more significant effects on the hand grip strength, QDASH, and SF-36 PCS scores than the LILT.